Could motor imagery training provide a novel load management solution for athletes? Recommendations for sport medicine and performance practitioners - McNeil, D. G.; Lindsay, R. S.; Worn, R.; Spittle, M.; Gabbett, T. J. (Sports Health: A Multidisciplinary Approach, 2025)
Context: Athletes often face the dual challenge of high training loads with insufficient time to recover. Equally, in any team, sports medicine and performance staff are required to progress training loads in healthy athletes and avoid prolonged reductions in training load in injured athletes. In both cases, the implementation of a well-established psychological technique known as motor imagery (MI) can be used to counteract adverse training adaptations such as excessive fatigue, reduced capacity, diminished performance, and heightened injury susceptibility.